Laboratory experiments on the influence of storm movement on overland flow - Lima, J. L. M. P. de (2003)
This study presents the results of laboratory experiments, conducted on an impermeable smooth plane surface with a movable sprinkling-type rainfall simulator, simulating a moving storm. In order to assess the effect of storm movement while eliminating variations in other factors that also influence the runoff response, the only parameters that were varied were storm velocity and direction. The results indicate considerable differences in runoff volumes and peaks and in overland flow hydrograph shapes, for storms moving upstream and downstream at differing velocities.